The critical success factors of event management : a focus on meetings, incentives, conventions & exhibitions (MICE) in Malaysia - Ismail, Firdaus (2014)
Malaysia Convention & Exhibition Bureau (MyCEB) reported MICE or Meetings, Incentives, Conventions and Exhibitions industry estimated to have economic impact of RM17.6 billion to the country as well as providing a total of 8,036 job opportunities for Malaysians. Currently, Malaysia has become one of the preferred destinations for MICE events. Consequently there is a significant need for managing and organizing MICE events so that they run smoothly and achieve the goals set. Thus, it is crucial to identify the Critical Success Factors (CSF) in organizing a MICE event. The study is primarily aimed at determining the Critical Success Factors in MICE event management. The study was conducted using qualitative approach and supported with quantitative approach. Through this approach, the Delphi technique has been adopted and a total of two (2) rounds of data collection was performed. Semi-structured interview technique was used in this study to get feedback fkom 15 MICE event managers. The study had identified six (6) CSF for a successful MICE event management, these factors are: clear objectives, location of venue, financial resources, code of conduct, marketing & promotion and event sponsorship. This study is expected to help the parties involved in event management to focus and pay attention to the six (6) critical success factors mentioned above for a successful MICE event management.